The impact of advertising on consumers’ buying behavior: the case of Safaricom Ethiopia, Addis Ababa, Ethiopia - Muluka Kedir Jemal; Kassegn Berhanu Melese (Cogent Social Sciences)
Advertising is a component of the promotional mix that is used to create awareness about goods and services and ultimately intends to influence buyers’ purchase decisions positively. The purpose of this study is to examine the impact of advertising characteristics of Impressiveness, Simple to Understand, Attention Grabbing, Memorable, Creative, and Honest on consumers’ buying behavior in telecommunications products and services. The study employed descriptive and explanatory research designs. A convenience sampling technique was implemented to select and administer 384 consumers of Safaricom Ethiopia. The findings of the study revealed that impressive, memorable, and creative advertisement characteristics have a statistically positive significant impact on consumer buying behavior, while simple-to-understand, attention-grabbing, and honest ads do not. The study helps marketers to gain a deeper understanding of how to influence consumers’ purchasing decisions. The study implies that marketers need to have consciousness for further marketing research development and the schemes for planning an efficient marketing strategy in responding to consumer needs.